IMPLEMENTASI KEBIJAKAN WAJIB BELAJAR SEMBILAN TAHUN DI DESA KADUARA TIMUR SUMENEP MADURA - Rini Aristin; Rina Nur Azizah (Universitas Tribhuwana Tunggadewi, 2018)
This study relates to the implementation of the Government Regulation of the Republic of Indonesia Number 47 of 2008 concerning Compulsory Education in the village of Kaduara Timur Sumenep Madura. The researcher uses the implementation model Edward III that the success of the policy according to Edwards III is influenced by four factors, namely, communication, resources, disposition, and bureaucracy. As well as the Koentjoroningrat theory to analyze local cultural values, that according to the Koentjoroningrat elements of culture consist of: (1) language, (2) knowledge systems, (3) social systems or social organizations, (4) living equipment and technology systems, (5) livelihood systems, (6) religious systems, (7) arts. This research is a descriptive research type of qualitative approach. This study describes the community's perspective on education policy in terms of the existing local culture, there is an influence of local culture on the policy. This type of research is a case study, research subjects use purposive sampling and incidental sampling. The researcher acts as an instrument that goes directly to the field to obtain data as accurately as possible, while also using interview, observation and documentation techniques. Data were analyzed using an interactive model (interactive models of analysis) Miles and Huberman which has three main components are: data reduction, data presentation, and draw a conclusion / verification.. The results of the study show that the implementation of the Government Regulation on nine-year compulsory education in Kaduara Timur Village has been going well. This is evidenced by 60% of the villagers who have already and are currently undergoing a normal nine-year education. The success of the government is influenced by the local culture which is still thick but in addition to the local culture the values that develop through the advancement of science and technology also have a special effect on the way of thinking of the people of Kaduara Timur village which then affects the awareness of the people of Kaduara Timur of the importance of education, especially nine years of basic education